Reflections from the Participation Sourcebook - World Bank (Washington, DC, 2012)
"The World Bank Participation Sourcebook " (report no. 15363) is a how-to guide to help Bank staff support participatory approaches in economic and social development. It is a collection of cases, told in the first person, by Task Managers in the Bank. In the Sourcebook examples, the sponsors and designers demonstrate a willingness to work collaboratively with other key stakeholders in carrying out the steps require to prepare a project for World Bank financing. Specifically, they: (a) identify the strengths and weaknesses of existing policies and service and support systems; that is the stakeholders conduct the analysis and diagnosis collaboratively; (b) decide and articulate what is needed; that is, the stakeholders collaboratively set objectives; (c) decide on pragmatic terms, directions, priorities, and institutional responsibilities; that is, the stakeholders create a strategy; and (d) develop or oversee development of project policies, specifications, blueprints, budgets, and technologies needed to move from the present to the future; that is, the stakeholders collaboratively formulate project tactics.